An empirical study on the estimation of software development effort with use case points - Alves, Luís M. (2013)
Empirical studies are important in software engineering to evaluate new tools, techniques, methods and technologies in a structured way before they are introduced in the industrial (real) software process. Perform empirical studies in a real context is very difficult due to various obstacles, so, we intend to create a stable environment that allows us to perform reliably empirical studies with students. This paper describes a case study with 104 students grouped in seven teams that developed a software system (Web application) for a real costumer. In this study we used a model based on Use Case Points (UCP) to estimate the resources needed to develop a software system.